2013
DOI: 10.1016/j.jsp.2013.08.002
|View full text |Cite
|
Sign up to set email alerts
|

Temperament in early childhood and peer interactions in third grade: The role of teacher–child relationships in early elementary grades

Abstract: Children's interactions with peers in early childhood have been consistently linked to their academic and social outcomes. Although both child and classroom characteristics have been implicated as contributors to children's success, there has been scant research linking child temperament, teacher-child relationship quality, and peer interactions in the same study. The purpose of this study is to examine children's early temperament, rated at preschool age, as a predictor of interactions with peers (i.e., aggre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
27
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 70 publications
(30 citation statements)
references
References 86 publications
3
27
0
Order By: Relevance
“…This is consistent with the notion of the teacher as creator of the social milieu of the classroom (wielding an "invisible hand"; Farmer, McAuliffe Lines, & Hamm, 2011), thus indirectly shaping the nature of interactions between children (Luckner & Pianta, 2011). Indeed, there is evidence that teachers' perceptions of children are related to children's interactions with peers (e.g., J. N. Hughes & Chen, 2011;Mercer & DeRosier, 2008;Rudasill et al, 2013). For example, Mercer and DeRosier (2008) found that teacher preference and peer rejection were bidirectionally associated across third and fourth grades.…”
Section: Temperament and Peer Interactionssupporting
confidence: 73%
“…This is consistent with the notion of the teacher as creator of the social milieu of the classroom (wielding an "invisible hand"; Farmer, McAuliffe Lines, & Hamm, 2011), thus indirectly shaping the nature of interactions between children (Luckner & Pianta, 2011). Indeed, there is evidence that teachers' perceptions of children are related to children's interactions with peers (e.g., J. N. Hughes & Chen, 2011;Mercer & DeRosier, 2008;Rudasill et al, 2013). For example, Mercer and DeRosier (2008) found that teacher preference and peer rejection were bidirectionally associated across third and fourth grades.…”
Section: Temperament and Peer Interactionssupporting
confidence: 73%
“…For example, previous studies indicated that positive indicators for affective TSRs and students' EBPs varied among students in kindergarten lower primary grades (LPG), and higher primary grades (Silver et al, 2005; HPG, Kuhns, 2008; Stewart and Suldo, 2011). In contrast negative indicators of affective TSRs and students' EBPs among kindergarten, LPG, and HPG students all showed similar phenomenon (Ezzell et al, 2000; Pianta and Stuhlman, 2004; Vick, 2008; Troop-Gordon and Kopp, 2011; Rudasill et al, 2013). Based on these findings, we expect age to moderate the link between affective TSRs and students' EBPs.…”
Section: Introductionmentioning
confidence: 88%
“…Teachers' positive relationships with children (e.g. close, sensitive, supportive) have been associated with children's positive peer interactions (Ladd 2005;Rudasill et al 2013). Considering the importance of teachers' scaffolding for children's peer interactions, in this study, we investigated how teachers' presence and social scaffolding were related to children's peer interactions in various classroom contexts.…”
Section: Introductionmentioning
confidence: 99%